Hubungan Antara Iklim Keselamatan dengan Perilaku Keselamatan pada Pekerja Proyek PLN PUSMAPRO PST JATENG I - Kumala, Charisha; Ramdhan, Doni Hikmat Hikmat (National Journal of Occupational Health and Safety, 2021)
A safety management system is crucial for the construction industry to effectively manage on-site safety, and its sustainability can be evaluated by analyzing the relationship between safety climate and safety behavior without waiting for accidents to occur. This study aimed to analyze this relationship among 120 workers at the PLN PUSMANPRO PST JATENG I electrical construction project. Using a cross-sectional design, primary data were collected through a Likert scale questionnaire adapted from previous validated studies. The results revealed that the safety climate was predominantly rated as low, and bivariate analysis indicated a positive and moderately strong correlation (P value = 0.000, correlation = 0.402) between safety climate and safety behavior. This finding suggests that improving the safety climate and providing adequate safety facilities can significantly influence workers' safety behavior, thereby reducing the likelihood of accidents on the project.